Analisis Usability Testing pada Sistem Informasi Dokumentasi dan Pelaporan Akreditasi - Zahra, Suci Khairatuz; Yulherniwati; Hadi, Ronal (JITSI : Jurnal Ilmiah Teknologi Sistem Informasi, 2024)
Study Program Accreditation is an effort to improve the quality of higher education institution services can be realized by building an information system and quality culture. This study was carried out to create an information system that is able to accommodate accreditation documentation and reporting in the Information Technology Department and analyzing usability testing with the system usability scale (SUS) and user interviews. The research results show that the average SUS score is 65. This score shows that users can accept information systems based on aspects of their usability. However, improving the quality of the application is still necessary, because the usability score also shows that the quality of the application is still at level D. Evaluation to improve application quality can begin by improving aspects of errors and satisfaction in the information system.